The missing voice of engagement: an exploratory study from the perspectives of case-managers at an early intervention service for first-episode psychosis - Rachel M. Tindall; Kelly Allott; Magenta Simmons; Winsome Roberts; Bridget E. Hamilton (BMC Psychiatry, 2019)
Abstract Background A key component of case-management in early intervention services for first-episode psychosis is engaging a person with the service and building a relationship from which therapy and treatment can be facilitated. The aim of this study was to understand how case-managers at an early intervention service experience the process of engagement and working with varying levels of attendance and participation. Methods Qualitative interviews were conducted with the case-managers of nine young people treated at an early intervention service for first-episode psychosis within 6 months of treatment entry. Interviews discussed the process of working with the young person and factors that influenced service engagement. Interviews were analyzed using thematic analysis. Results Case-managers described a range of influences on engagement which were grouped under the themes: young person and caregiver influences on engagement, case-manager influences on engagement, and influences of the early intervention service system on engagement. The experience of engagement was described as relational, however it occurred in the context of broader influences, some of which were unable to be changed or challenged by the case-manager (e.g., resource allocation, models of treatment, young person demographics). Conclusion This study illustrates the challenges that case-managers face when working with young people with first-episode psychosis, and the direct influence this has on engagement with treatment. Understanding these challenges and addressing them in policy and service design may lead to improvements in young peoples’ recovery from first-episode psychosis and increase case-manager job satisfaction.